2017
DOI: 10.1016/j.ibmb.2017.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation, analysis of expression and localisation of circadian clock genes from the perspective of photoperiodism in the aphid Acyrthosiphon pisum

Abstract: Aphids are typical photoperiodic insects that switch from viviparous parthenogenetic reproduction typical of long day seasons to oviparous sexual reproduction triggered by the shortening of photoperiod in autumn yielding an overwintering egg in which an embryonic diapause takes place. While the involvement of the circadian clock genes in photoperiodism in mammals is well established, there is still some controversy on their participation in insects. The availability of the genome of the pea aphid Acyrthosiphon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 75 publications
(145 reference statements)
0
21
0
Order By: Relevance
“…The distribution of Ptth‐ expressing neurones was very similar to that of a particular subset of dorsal clock neurones (DNs) known as large DNs (l‐DNs) that express the circadian clock gene timeless (Barberà et al ., ). In order to test the possibility that these l‐DNs were expressing Ptth in addition to the clock gene timeless , we carried out a simultaneous localization with two different probes against transcripts of both timeless and Ptth genes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The distribution of Ptth‐ expressing neurones was very similar to that of a particular subset of dorsal clock neurones (DNs) known as large DNs (l‐DNs) that express the circadian clock gene timeless (Barberà et al ., ). In order to test the possibility that these l‐DNs were expressing Ptth in addition to the clock gene timeless , we carried out a simultaneous localization with two different probes against transcripts of both timeless and Ptth genes.…”
Section: Resultsmentioning
confidence: 99%
“…B–G). As already reported for other in situ hybridizations of aphid brains with different riboprobes (Barberà et al ., ), unspecific staining of tracheae with both sense and antisense Ptth probes was observed (Fig. A, D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the aphid Megoura viciae, the site of photoreception for initiating sexual morphs under decreasing photoperiods in late summer has also been localized to the dorsal brain (Lees 1964). More recent studies in the pea aphid, Acyrthosiphon pisum, identified the clock genes and revealed that A. pisum possesses also mammalian-type and Drosophila-type clock genes that are expressed in the dorsal brain, but additionally also in the lateral brain (Cortés et al 2010;Barberà et al 2017). The location of the master clock in mosquitoes is less well studied.…”
Section: Photoentrainment In Moth Butterflies Aphids and Mosquitoesmentioning
confidence: 99%
“…Several behavioural studies suggest the existence of a functional circadian clock in sexual as well as in parthenogenetic aphid forms of various aphid species 19 , 20 , although the experimental protocols did not allow to investigate damping of the clock. More recently, two studies identified putative clock genes and the location of clock gene expressing neurons in the pea aphid Acyrthosiphon pisum ( Harris ) 21 , 22 . Unfortunately the challenge to uncouple the aphid’s activity from the plant’s influence remained unattended in most studies.…”
Section: Introductionmentioning
confidence: 99%